The Impact of the MSME’s marketing to the Customer Satisfaction in Micro, Small, and Medium Restaurant in Surabaya - Ivana Patricia (iBuss Management, 2018)
The MSMEs have long been recognized as the most important agent of the economic growth as they cover 99% of total Indonesia’s business, and provide more than 97% of Indonesia’s total full employment. As the second biggest city in Indonesia after Jakarta, the micro, small, and medium enterprises in Surabaya are mostly dominated by restaurant businesses which contribute more than 40% to Surabaya economy.However as the number of restaurants in Surabaya is always increasing every year, hence scholar suggests that the restaurant businesses, especially the micro, small, and medium ones should carefully formulate and implement their marketing strategies in order to sustain. This study supports the view that due to the unique characteristic and the limited resources that MSMEs are facing, it is inappropriate to assume that MSMEs can adopt the same marketing practices as the large enterprises. Research suggests that MSME’s marketing consists of four elements namely personal branding, perseverance, practice and co-production.Data that have been gathered and analyzed from the respondents showed that MSMEs marketing significantly influences the customer satisfaction in the micro, small, and medium restaurants in Surabaya. Keyword:MSMEs marketing, Customer Satisfaction, personal branding, perseverance, practice and co-production